Fatal Feline Rabies: A Case Report of Encephalitis Following a Cat Scratch in an Endemic Indonesian Region - Gede Tamblang Baswara Putra; I Made Mahardika Yasa (HM Publisher, 2025)
Background: Rabies, a viral zoonosis caused by Lyssavirus, remains a significant public health threat, particularly in Asia and Africa, with an almost invariably fatal outcome once clinical symptoms manifest. While dogs are the primary vector, transmission via cats, especially through scratches, is an under-recognized risk in endemic areas like Indonesia. Delayed post-exposure prophylaxis (PEP) and gaps in surveillance contribute to ongoing fatalities. Case presentation: We report the case of a 45-year-old Indonesian male from a rural, rabies-endemic area in Jembrana Regency, Bali, who developed fatal encephalitis. Approximately one month prior to symptom onset, he sustained a superficial scratch on his right hand from a free-roaming domestic cat. He did not seek immediate medical attention or PEP. His illness commenced with prodromal symptoms of fever and headache, rapidly progressing to agitation, dysphagia, severe hydrophobia, and aerophobia. Neurological examination revealed fluctuating consciousness, hyperactive reflexes, and marked autonomic dysfunction. Despite intensive supportive care in an isolation unit, his condition deteriorated, leading to death two days after admission. A clinical diagnosis of rabies encephalitis was made based on the characteristic symptoms, a clear history of exposure to a potential vector, and the epidemiological context. Conclusion: This case underscores the critical importance of recognizing cats as significant vectors for rabies transmission, even via non-bite exposures like scratches, particularly in endemic settings. It highlights the urgent need for increased public awareness regarding prompt wound management and PEP for all potential rabies exposures, including those from felines. Furthermore, comprehensive rabies control strategies must incorporate feline vaccination and improved surveillance to effectively mitigate this fatal disease in regions like Indonesia.